Effect of Acupuncture on Functional Connectivity of the Limbic Network in Patients with Knee Osteoarthritis: A Resting State Functional Magnetic Resonance Imaging Study - Wu N; Lou XS; Chang YN; Li JY; Zhang ZH; Hu JH; Fan Y; Feng XD; Yin S (Journal of Pain Research)
Nan Wu,1,* Xia-Shuang Lou,1,* Yi-Niu Chang,2,* Jing-Yi Li,1 Zhen-Hua Zhang,3 Jia-Hui Hu,3 Yue Fan,3 Xiao-Dong Feng,1,3 Shuai Yin3 1School of Rehabilitation Medicine, Henan University of Chinese Medicine, Zhengzhou, Henan, 450046, People’s Republic of China; 2Zhengzhou Railway Vocational & Technical College, Zhengzhou, Henan, 451460, People’s Republic of China; 3Rehabilitation Center, The First Affiliated Hospital of Henan University of Chinese Medicine, Zhengzhou, Henan, 450000, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xiao-Dong Feng, The First Affiliated Hospital of Henan University of Chinese Medicine, No. 19, Renmin Road, Zhengzhou, 450000, People’s Republic of China, Tel +8615303828605, Email fxd0502@163.com Shuai Yin, The First Affiliated Hospital of Henan University of Chinese Medicine, No. 19, Renmin Road, Zhengzhou, 450000, People’s Republic of China, Tel +8613458588608, Email yinshuai880910@163.comBackground: Knee osteoarthritis (KOA) is a prevalent degenerative joint disorder. Acupuncture therapy demonstrates significant efficacy in alleviating KOA symptoms. However, the central neuroimaging mechanisms underlying acupuncture’s therapeutic effects remain incompletely elucidated. This study investigated brain network differences between KOA patients and healthy controls and further examined the effects of acupuncture on aberrant functional connectivity (FC) within brain networks in KOA patients.Patients and Methods: Blood Oxygenation Level Dependent functional Magnetic Resonance Imaging (BOLD-fMRI) combined with Independent Component Analysis (ICA) was employed to investigate resting-state functional connectivity differences between 45 KOA patients and 15 healthy subjects. KOA patients were then randomized to: acupuncture group, placebo acupuncture group, or waiting for treatment group. After the intervention, the BOLD-fMRI scan was performed again, the influence of different intervention methods on the brain functional connectivity of KOA patients was investigated by ICA, and the central mechanism of acupuncture treatment of KOA was studied.Results: Baseline KOA patients showed significantly reduced FC in the limbic network versus healthy subjects, specifically in the right temporal pole, right parahippocampal gyrus, right hippocampus, bilateral anterior cingulate gyrus, right amygdala, right orbital part of the inferior frontal gyrus, bilateral medial and paracingulate gyrus. Clinically, the acupuncture group showed significantly greater improvement in pain and mobility than both the placebo acupuncture group and waiting for treatment group (p < 0.05). Neuroimaging revealed that only the acupuncture group demonstrated significantly increased FC post-intervention in key limbic regions, including the anterior cingulate gyrus, lenticular putamen, amygdala, temporal pole, hippocampus, pallidum, parahippocampal gyrus and caudate nucleus.Conclusion: Reduced limbic network functional connectivity is a central pathological feature in knee osteoarthritis. Acupuncture’s therapeutic efficacy is mediated primarily by focal neuromodulation restoring these aberrant limbic connectivity patterns. In contrast, placebo acupuncture exerts its placebo effects primarily through engagement of the reward circuitry.Keywords: acupuncture, functional magnetic resonance imaging, independent component analysis, limbic system, osteoarthritis, knee